Radiocarbon chronology of the Neolithic-Eneolithic period in the Karelian Republic (Russia) - Alexey Yur'evich Tarasov; Kerkko Nordqvist; Teemu Mökkönen; Tatyana Khoroshun (Documenta Praehistorica, 2017)
This article discusses a radiocarbon-based chronology for the Neolithic–Eneolithic period in the present-day Republic of Karelia (Russian Federation). The main goal is to present all currently available radiocarbon datings, including the previously published dates, as well as the ones recently obtained by the authors. In total, there are 194 dates from 77 sites covering the period from the 6th to the 2nd millennium cal BC. Besides providing an up-to-date list of datings, the article also evaluates their reliability and utility in building a local chronology. Despite several shortcomings, the new AMS-supported chronology enables the study of past cultural dynamics in much greater detail than previously and allows its better integration into the wider north-east European chronological framework.